The Insect and the Image : Visualizing Nature in Early Modern Europe, 1500-1700 - Neri, Janice (Book collections on Project MUSE., 2011)
Once considered marginal members of the animal world (at best) or vile and offensive creatures (at worst), insects saw a remarkable uptick in their status during the early Renaissance. This quickened interest was primarily manifested in visual images--in illuminated manuscripts, still life paintings, the decorative arts, embroidery, textile design, and cabinets of curiosity. In The Insect and the Image, Janice Neri explores the ways in which such imagery defined the insect as a proper subject of study for Europeans of the early modern period. It was not until the sixteenth century that insects b.